Alcohol Consumption and Violent Offending: Findings From a Longitudinal Study on Korean Youth from Mid to Late Adolescence - Lee, Yeungjeom (Criminal justice and behavior, 2023)
Although past research highlights a close relationship between alcohol and crime, its role as a static (i.e., stable) and dynamic (i.e., changing) risk factor of violent delinquency has been less studied. Cross-lagged dynamic panel models were employed to address this issue based on a longitudinal Korean adolescent sample. Despite the significant independent effects of baseline individual differences in alcohol use, its impact on violence was no longer statistically significant when accounting for within-individual changes in alcohol consumption. However, we also found interaction effects between baseline and within-individual changes in alcohol consumption; youth who consume more alcohol at earlier ages and engage in more alcohol use over time are more likely to engage in violence. Findings stress the importance of studying static and dynamic factors and their interaction to provide a greater understanding of violent delinquency. Limitations and implications for policy and practices are discussed.